Expression and trafficking of placental microRNAs at the feto‐maternal interface. Issue 7 (13th March 2017) - Chang, Guojing; Mouillet, Jean‐François; Mishima, Takuya; Chu, Tianjiao; Sadovsky, Elena; Coyne, Carolyn B.; Parks, W. Tony; Surti, Urvashi; Sadovsky, Yoel
ABSTRACT: During pregnancy, placental trophoblasts at the feto‐maternal interface produce a broad repertoire of microRNA (miRNA) species. These species include miRNA from the primate‐specific chromosome 19 miRNA cluster (C19MC), which is expressed nearly exclusively in the placenta. Trafficking of these miRNAs among the maternal, placental, and fetal compartments is unknown. To determine miRNA expression and trafficking patterns during pregnancy, we sequenced miRNAs in triads of human placenta and of maternal and fetal blood and found large subject‐to‐subject variability, with C19MC exhibiting compartment‐specific expression. We therefore created humanized mice that transgenically express the entire 160‐kb human C19MC locus or lentivirally express C19MC miRNA members selectively in the placenta. C19MC transgenic mice expressed a low level of C19MC miRNAs in diverse organs. When pregnant, female C19MC mice exhibited a strikingly elevated (>40‐fold) expression of C19MC miRNA in the placenta, compared with other organs, that resembled C19MC miRNAs patterns in humans. Our mouse models showed that placental miRNA traffic primarily to the maternal circulation and that maternal miRNA can traffic to the placenta and even into the fetal compartment. These findings define an extraordinary means of nonhormonal, miRNA‐based communication between the placenta and feto‐maternal compartments.—Chang, G., Mouillet, J.‐F., Mishima, T., Chu, T., Sadovsky, E., Coyne, C. B., Parks, W. T., Surti, U., Sadovsky, Y. Expression and trafficking of placental microRNAs at the feto‐maternal interface. FASEB J. 31, 2760–2770 (2017). www.fasebj.org